Microglia Susceptibility to Free Bilirubin Is Age-Dependent - Vaz, Ana Rita (2020)
Funding: This work was supported by National Funds (Fundacão para a Ciencia e a Tecnologia—UID/DTP/04138/2015-2019) to iMed.ULisboa. AF had a post-doctoral research position (C2007-FFUL/UBMBE/02/ 2011) and AV a post-doc fellowship (SFRH/BPD/76590/2011), both granted by FCT. CS and ES were Master students from University of Bologna who developed their thesis at Universidade de Lisboa, with fellowships from Erasmus+ Programme. We thank Professor Stefano Girotti from the University of Bologna for establishing such collaborative Program and for the local supervision of the students. The funding organization had no role in data collection and analysis, decision to publish, or preparation of the manuscrip